An integrated solution for protection and automation of power systems - Lehtonen, M; Antila, E; Seppanen, M (14th International Conference and Exhibition on Electricity Distribution (CIRED 1997 - Distributing Power for the Millennium), 1997)
The paper presents an integrated solution for power system protection and medium voltage network and substation automation. For network automation, the remote control and monitoring of sectionalizing and tie switches is discussed. With regard to the substation automation, the integration of numeric protective relays into the substation telecontrol system (SCADA) is studied. A solution is presented where the protective relays are connected to the station computer via a fibre-optic based local area network. The station computer, in turn, works as a remote terminal unit of the telecontrol system. (5 pages)